Saudi regions system in the balance of local administration - EL-DEEP, FOUAD (Journal of Economic, Administrative and Legal Sciences, 2020)
The research aimed to monitor the origin and development of the regions as the first level in the Saudi local administration system, study its current division, and ensure the effectiveness of its councils competencies and the extent of democracy in its formation method. This study based on the descriptive-analytical approach, to analyze the past and present of the regions and their councils, and describe the problems of their law, to determine the reforms that must be introduced to develop and improve this system. Results: The Saudi legislator did not grant the regions and their councils’ legal personality, the current zoning - size and population - is not consistent with efficiency administrative, and the selection of all members of the region’s council by appointment weakened popular participation. Recommendations: Grant the regions and their councils’ legal personality, give them financial independence, reset zoning, select a part of the members of the council of regions by-election and activate the region’s councils’ jurisdictions.